Is the Impact of Starvation on the Gut Microbiota Specific or Unspecific to Anorexia Nervosa? A Narrative Review Based on a Systematic Literature Search - Mack, Isabelle; Penders, John; Cook, Jessica; Dugmore, Jaslyn; Mazurak, Nazar; Enck, Paul (Current Neuropharmacology, 2018)
Background: The role of the gut microbiota in Anorexia Nervosa (AN) has long been neglected by researchers, although the fact that the former is known to play an important role in health, disease and weight regulation. Cycles of overweight and underweight due to natural states of starvation and refeeding are normal in many vertebrates in their ecological niches. Objective: The aim of this review was to compare the similarities and differences of the gut microbiota in eating disorders with conditions of fasting and refeeding in other vertebrates. Method: A systematic literature search was conducted in Pubmed and Web of Science to find all relevant studies examining the gut microbiota in eating disorders and different states of fasting in vertebrates for this narrative review. Results: Gut microbiota appears to differ in AN versus normal-weight individuals. Induced fasting conditions in other vertebrates resulted in heterogeneous effects on gut microbiota with respect to their richness, diversity and community structures. The findings for hibernating animals were generally consistent. A decrease in microbial richness and diversity was observed in the hibernating animal compared to the active animal, and the community structures were linked to these conditions. Some similarities and differences between AN and different states of fasting in other vertebrates were found. Conclusion: The complexity of the relationship between fasting and gut microbiota is difficult to interprete. A deeper biological understanding is necessary to identify promising approaches for the modulation of the AN gut microbiota to support established psychotherapies.
Keywords: caloric restriction